Versatile coordination modes of 2-(Diformylmethylene)-3,3-dimethylindole towards late-transition-metal ions: C-H bond activation and formation of cyclic acyl-palladium(ii) complexes - Khaledi, H.; Olmstead, M.M.; Ali, Hapipah Mohd (2011)
The reaction of the potential multidentate ligand, 2-(diformylmethylene)-3,3-dimethylindole (diformyl), with M(OAc)(2) (M = Co-II, Ni-II, Cu-II, Zn-II, Cd-II, and Pd-II) afforded a series of metal complexes with different nuclearity in which the mono-deprotonated diformyl behaves as an N,O-bidentate chelate or N,O,O-tridentate chelating-bridging agent. The bonding modes of the ligand and thus the structures could be modified to some extent by further treatment of the complexes with an ancillary ligand (methanol, pyridine, or 4,4'-bipyridine). In the case of the palladium(II) complex, the pyridine and 4,4'-bipyridine adducts yielded C, N-chelation of the metal ion through the aldehyde carbon and indolic nitrogen of the doubly deprotonated diformyl. The resulting acylpalladium complexes were further bridged into polymeric structures when the dianionic diformyl behaved as a C, N, O-chelating-bridging ligand.